2003
DOI: 10.1124/mol.63.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Tonically Activated GABAA Receptors in Hippocampal Neurons Are High-Affinity, Low-Conductance Sensors for Extracellular GABA

Abstract: In the hippocampus, two distinct forms of GABAergic inhibition have been identified, phasic inhibitory postsynaptic currents that are the consequence of the vesicular release of GABA and a tonic conductance that is activated by low ambient concentrations of extracellular GABA. It is not known what accounts for the distinct properties of receptors that mediate the phasic and tonic inhibitory conductances. Moreover, the physiological role of the tonic inhibitory conductance remains uncertain because pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 35 publications
9
142
1
2
Order By: Relevance
“…Propofol acts at GABA A receptors where it increases both decay times and the open channel probability (Kitamura et al, 2004) and slows desensitization (Bai et al, 1999;Bai et al, 2001). Diverse expression and the multitude of naturally occurring sub-unit combinations of GABA A receptors make it difficult to predict anesthetic sensitivity and mechanisms (Yeung et al, 2003). This receptor diversity differs prominently across brain regions and is thought to be responsible for pharmacological differences between phasic and tonic GABA receptor mediated currents within and across neurons (Yeung et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Propofol acts at GABA A receptors where it increases both decay times and the open channel probability (Kitamura et al, 2004) and slows desensitization (Bai et al, 1999;Bai et al, 2001). Diverse expression and the multitude of naturally occurring sub-unit combinations of GABA A receptors make it difficult to predict anesthetic sensitivity and mechanisms (Yeung et al, 2003). This receptor diversity differs prominently across brain regions and is thought to be responsible for pharmacological differences between phasic and tonic GABA receptor mediated currents within and across neurons (Yeung et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse expression and the multitude of naturally occurring sub-unit combinations of GABA A receptors make it difficult to predict anesthetic sensitivity and mechanisms (Yeung et al, 2003). This receptor diversity differs prominently across brain regions and is thought to be responsible for pharmacological differences between phasic and tonic GABA receptor mediated currents within and across neurons (Yeung et al, 2003). In this context, our goal in the present studies was to try to identify the potential targets for anesthetic actions in adult NTS neurons with fully mature development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade, several studies have shown that GABA A receptor activation can also mediate tonic inhibition; these receptors are extrasynaptically and perisynaptically localized and contain a distinct, high affinity subunit composition made of δ and α4, α5 & α6 subunits (Nusser et al, 1998;Yeung et al, 2003;Semyanov et al, 2003Semyanov et al, , 2004Cope et al, 2005;Scimemi et al, 2005;Glykys et al, 2008). Hence, GABA A receptors can generate two types of current, depending on their location and subunit composition: the first type is the classic synaptic phasic (or 'transient') current that results from the release of GABA from synaptic vesicles in the synaptic cleft; the second type is a tonic ('always on') current that is caused by GABA A receptors responding to low levels of ambient GABA (Farrant and Nusser, 2005).…”
Section: Gaba a Receptor-mediated Tonic Inhibitionmentioning
confidence: 99%